Application study on fiber Bragg grating sensors in damage monitoring of sandwich composite joints. (June 2020) - Zeng, Haiyan; Yan, Renjun; Xu, Lin; Gui, Siyuan
This article studies the application of fiber Bragg grating sensors in damage monitoring of sandwich composite L-joints, which aims to reveal the interface damage between the GFRP skin and the foam core. Fiber Bragg grating sensors have been arranged based on numerical results. The ultimate load and failure location via numerical modelling have been experimentally verified. Strains measured by fiber Bragg grating sensors have shown anomalies with load increased, indicating the onset and propagation of damage. Based on the damage-induced strain anomalies, four stages have been addressed to reveal the emergence, accumulation and propagation of damage during the loading process. Measurements by numerical simulation and surface mounted strain gauges have been found to be less sensitive to internal damage, proving the great significance of embedding fiber Bragg grating sensors to monitor interface damages of sandwich L-joint.